2015
DOI: 10.1016/j.jtcvs.2014.08.086
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results and predictors of survival after surgical resection of patients with lung cancer and interstitial lung diseases

Abstract: In these patients, there are competing risks of death. Wedge resection reduced death caused by respiratory failure but resulted in poorer long-term prognosis than lobectomy. For patients with poor predictors of survival, such as predicted percent vital capacity of 80% or less, surgical resection should be limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
103
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(108 citation statements)
references
References 22 publications
1
103
4
Order By: Relevance
“…They concluded that history of AE, surgical procedure, UIP pattern in CT imaging, male gender, preoperative steroid use, elevated serum KL-6, and low vital capacity were risk factors for AE of IP in lung cancer patients following a pulmonary resection. In other reports, the same group also presented scores for predicting AE of IP following a lung resection [13] as well as their long-term results [14]. In our study, these factors, except for PP, were not found to significantly increase the risk of AE after lung resection.…”
Section: Discussionsupporting
confidence: 63%
“…They concluded that history of AE, surgical procedure, UIP pattern in CT imaging, male gender, preoperative steroid use, elevated serum KL-6, and low vital capacity were risk factors for AE of IP in lung cancer patients following a pulmonary resection. In other reports, the same group also presented scores for predicting AE of IP following a lung resection [13] as well as their long-term results [14]. In our study, these factors, except for PP, were not found to significantly increase the risk of AE after lung resection.…”
Section: Discussionsupporting
confidence: 63%
“…Sublobectomy, including wedge resection and segmentectomy, is oncologically compromised resection of peribronchial, hilar, and mediastinal lymph nodes . Sublobectomy with low rates of nodal sampling could underestimate the tumor stage . Similarly, Robson et al reported that SBRT might be associated with significant regional control failure and worse outcomes as a result of occult pathological nodal metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The approach using the 8-week volume decrease as an early marker is also applicable to cohorts treated with third-generation EGFR-TKIs, including rociletinib, AZD9291, and HM61713, in ongoing trials 35, 36 . The now validated association between the 8-week volume decrease and survival in the erlotinib or gefitinib treated cohorts may contribute to early assessment of the efficacy and therapeutic benefit of these novel agents, by providing additional information beyond the RECIST-based evaluations.…”
Section: Discussionmentioning
confidence: 99%